Konflik Batin Tokoh Paijah dalam Naskah Drama Malam Jahanam Karya Motinggo Boesje - Rian Dwiyanto; Muhamad Irgi Abdillah Az-zarkasyi (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
Literary works are cultural products that are believed to be able to communicate the inner experiences of an author to life's problems, both as creators and as part of local community groups. The script for the drama Malam Jahanam by Motinggo Boesje is one of the literary works whose content sheds a lot of inner experiences. One of them is Paijah. The character Paijah is the only female character in the drama script Malam Jahanam by Motinggo Boesje. Paijah's character also experiences many inner conflicts in the drama. The purpose of this research is to describe the inner conflict of the character Paijah in the drama script Malam Jahanam by Motinggo Boesje using the branch of Literary Psychology. This research was conducted using a descriptive qualitative method. The data used for this study are in the form of dialogues and monologues conveyed by the character Paijah in the play. From the results of this study, there are several forms of inner conflict experienced by the character Paijah, including fear, anger, hurt, and panic. These factors cause the inner conflict of Paijah's character to Mat Kontan as her husband, Soleman as her lover, and Utai can occur.